Data palveluna -malli - Suutari, Samuli (2020)
Data as a Service is a cloud computing service model based on the cloud computing architecture. The intends to combine and manage data based on several different data sources in order to provide the end user with a data product for a specific purpose that is scalable and accessible anywhere and on any device. The aim of this thesis was to present the concept of cloud computing and it’s most service models. In addition, it was intended to introduce the Data as a Service model, it’s features, use scenarios and the biggest challenges related to it’s use. This thesis can be used as a basis for future research of the subject in the future, and it was conducted as a literature review. While conducting the thesis, it became apparent that the features and advantages of the Data as a Ser-vice model are similar to those of the other cloud computing service models. However, there are several challenges related to use of the service model be-fore it can become more common, the most important being questions related to privacy and data quality. The advantages of the model are its capability to store, combine and manage data from several different data sources and for-mats. At the same time, the service providers need to be able to ensure that all privacy regulations are followed. The continuous expansion of data production is also a challenge to service providers, and in order to compete, the data quality challenges need to be addressed.